PENINGKATAN KETRAMPILAN MEMBACA PEMAHAMAN MELALUI SQ3R PADA SD NEGERI SIDOMUKTI TAHUN PELAJARAN 2020/2021 - Darojah, Ayuna Kurnia (CV Sintesia, 2024)
This study aims to improve students' reading comprehension skills through the SQ3R method in the 2020/2021 school year. The research carried out was classroom action research (PTK). This classroom action research was conducted in 2 cycles with two meetings for each cycle. Each cycle consists of 4 stages including: planning, implementing, observing and reflecting. This research was conducted online and offline with 23 students as research subjects. The independent variable is the SQ3R method and the dependent variable is learning outcomes. The research instruments were tests, observations, documentation. The analysis techniques used are qualitative and quantitative analysis techniques. The results of students' reading ability in the pre-cycle with an average of 55.17 increased 18.52% to 65.39 in the first cycle, an increase of 13.13% to 78.52 in the second cycle. These results indicate that the SQ3R method has improved.